PEEK as a replacement for CoCrMo in knee prostheses: Pin-on-disc wear test of PEEK-on-polyethylene articulations. (September 2021) - Heuberger, Roman; Stöck, Christina; Sahin, Jeannine; Eschbach, Lukas
Abstract: The feasibility to use poly-ether-ether-ketone (PEEK) instead of CoCrMo for femoral condyles of knee prostheses was investigated in this pin-on-disc study. This replacement would hinder the release of the toxic elements Co, Cr and Mo and this possibly at lower production costs. In this preliminary pin-on-disc study, the wear of the pairings PEEK vs. ultra-high-molecular-weight polyethylene (UHMWPE) and PEEK vs. vitamin E containing crosslinked polyethylene (XLPE) was investigated in unidirectional and multidirectional wear tests. The articulating surfaces of the pins and discs were polished after the wear tests, while most of the initial toolmarks were removed. In addition, there were small scratches on the surfaces. Striations and protuberances were found on some of the UHMWPE samples. All wear factors were relatively small with less than 1 × 10 −6  mm 3 /Nm. Due to the low wear, the resulting weight loss was highly affected by the soaking of the samples. This was especially the case for the discs due to their larger surface. Thus, the wear of the discs was not used for the comparisons. The wear factors for PEEK pins and XLPE pins were in the range of (0.05 to 0.06) × 10 −6  mm 3 /Nm, both for unidirectional and multidirectional motion. The wear of the UHMWPE pins was with (0.07 ± 0.01) × 10 −6  mm 3 /Nm slightly higher under unidirectional motion and with (0.28 ± 0.03) × 10 −6  mm 3 /Nm four times higher under multidirectional motion. Thus, PEEK should be considered as an alternative to the CoCrMo alloy in knee prostheses, especially when used in combination with XLPE liners. Highlights: Pin-on-disc wear study with the pairings PEEK vs. UHMWPE and PEEK vs. XLPE, both in uni- and multidirectional motion. Low wear for the PEEK and XLPE samples, both in uni- and multidirectional wear tests. Slightly higher wear for the UHMWPE samples under unidirectional motion and 4× higher under multidirectional motion. Surface characterisation providing kernel roughness values, which describe the tribological surfaces in detail.